El desarrollo del pensamiento crítico en el proceso de enseñanza aprendizaje, en los niños y niñas del sexto año de educación general básica, de la escuela fiscal mixta Mariscal Antonio José de Sucre, de la provincia de Cotopaxi, ciudad de Saquisili, durante el año lectivo 2014-2015 - Carrera Defaz, Ibeth del Rocío (2015)
This research was designed a methodological guide of stimulation exercises based on Critical Thinking Development in the Teaching-Learning Process. The research problem was in which way the critical thinking development stimulates the teaching learning process in sixth children of general basic education at Mariscal Antonio Jose de Sucre School, Cotopaxi province, Saquisilí city, during 2014-2015. The methods applied in the research were deductive and inductive, the deductive method was to study the research variables in the fundamental categories while the inductive method in analysis and interpretation of results and the conclusion of field research. The conclusions of this one determined that the majority of children do not think themselves they repeat the same activities as their partners and these activities do in mechanical way because of the monotonous and boring classes. The main objective is the design of a methodological guide of stimulation exercises based on critical thinking development in the teaching learning process.